Efforts to improve village cleanliness in preventing Covid-19 in Pilobuhuta Village, Batudaa District - Anwar, Herson; Otaya, Lian; Babay, Regianti; laubaha, wiya; Yusuf, Sri Agustin (BADAN PENERBIT STIEPARI PRESS, 2022)
This service activity examines